Optical and Electrical Properties of Undoped and Cu-Doped p-Bi2S3 Films Deposited by Chemical Bath Deposition - He, H.-Y. (Recent Patents on Materials Science, 2017)
Background: Bismuth sulfide (Bi2S3) has many smart physical and chemistry properties and potential advantages in optical and electrical applications. To further enhance the application property, many studies had been performed. Objective: This work explained the manufacturing and potential application of the Bi2S3 materials with various cation dopings in recent literature and patent and then focused on the deposition and Cu doping effect of the Bi2S3 films. Method: Undoped and Cu-doped Bi2S3 films were deposited by a modified chemical bath deposition and characterized by X-ray diffraction, scanning electron microscopy, ultraviolet-visible spectrophotometry, photoluminescence spectrophotometry, and electrical conduction measurement. Results: The Cu-doping resulted in direct and indirect optical bandgaps, which first increased and then decreased with Cu-doping content. Moreover, the films showed S/Bi>1.5, p-type conduction, and low electrical resistance. The Cu doping led to a decrease in the resistance by increasing Cu content. The films also showed strong bandgap emission and two weak visible emissions related to the defects. The refractive index, extinction coefficient, optical conductivity, and dielectric constant of the films were calculated from the transmittance and reflectance spectra. The present article discussed some important patents related to Bi2S3 thin films Conclusion: By controlling the S/Bi ratio and doping appropriate amount of Cu cation, the optical and electrcical properties can be tuned and enhanced.
Keywords: optical property